Bahasa Guru dalam Pembelajaran Bahasa Jerman di SMA - Cindy, Febia Dwiana; Rosyidah, Rosyidah (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2020)
This article is a result of literature review that aims to explain teacher talk in context of teaching and learning German as a foreign language at senior high schools. Therefore, some relevant theories are studied, reviewed, compared and presented by the author in order to obtain the aims of this research. The result showed that teaching and learning German as a foreign language, German language should be applied by the students not only as a learning object but also as their daily practice. German language as the teacher talk has a broad influence towards students’ German learning outcomes. Based on the general purpose of teacher talk, which is to make the delivered message easily understood by the students, teachers use modified German language in teaching and learning process. In this case, teachers modify their language to fit the students’ German skill by considering the linguistic order such as simplifying sentences, talking slowly, making the clearer articulation, and using vocabulary that has been known by the students. To discover the tendency of German language used by teachers in class, it is necessary to analyze teacher talk. To analyze teacher talk we can use Flanders Interaction Analysis Categories (FIAC). It is one of the instruments of social interaction analysis.